Toxicity Test of Acehnese Plants Using The Brine Shrimp Lethality Test (BSLT) Method - Mastura Mastura; Mauliza Mauliza; Hasby Hasby (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2022)
his study aimed to determine the potential toxicity of the ethanol extract of typical Acehnese plants to shrimp larvae (Artemia salina Leach) using the Brine Shrimp Lethality Test (BSLT) method as indicated by the LC50 value. This study used 1,080 shrimp larvae divided into four groups (three groups of extract concentration series and one negative control group). Each group consists of 15 larvae with three repetitions (triple) of treatment. The four treatment groups were given the suspension of ethanol extract of Cananga flower and leaf extract (Cananga odorata), jeumpa flower and leaf (Michelia alba), and Tanjung flower and leaf (Mimusops elengi) with concentrations of 1000 ppm, 100 ppm, and 10 ppm. The mortality data of shrimp larvae were analyzed by probit analysis to determine the LC50 value. The result of this research is that the ethanol extract of the Cananga flower and leaf (Cananga odorata) has LC50 values of 55.71 ppm and 79.43 ppm, respectively. The ethanol extract of the jeumpa flower and leaf (Michelia alba) had LC50 values of 831.76 ppm and 398.10 ppm, respectively. The ethanol extract of the Tanjung flower and leaf (Mimusops elengi) had LC50 values of 295.12 ppm and 77.67 ppm, respectively.